Cross-Cultural Sex/Gender Differences in Produced Word Content Before the Age of 3 Years. (April 2023) - Wallentin, Mikkel; Trecca, Fabio
Does sex/gender matter for language acquisition? Small advantages in vocabulary size for females are well documented. In this study, however, we found that children's early vocabulary composition was a significantly better predictor of sex/gender than their vocabulary size. We conducted classification analysis on word-production data from children (12–36 months old, n = 39, 553) acquiring 26 different languages. Children's sex/gender was classified at above-chance levels in 22 of 26 languages. Classification accuracy was significantly higher than for models based on vocabulary size and increased as a function of sample size. Boys produced more words for vehicles and outdoor scenes, whereas girls produced more words for clothing and body parts. Classification accuracy also increased as a function of age and peaked at 30 months, reaching accuracy levels observed in studies of adult word use. These differences in vocabulary are indicative of differences in the lifeworld of children and may themselves cause further differences in development.